(untitled) (Applied Biological Research, 2017)
A field experiment was conducted to study effect of sowing dates, varieties and weed control methods on growth, yield and water productivity of direct seeded rice (DSR) in a split plot design. Crop growth rates were higher during 60-90 DAS and were positively correlated with grain yield. Grain yield of DSR sown on the day of nursery sowing was at par with transplanted rice. It saved 69 cm irrigation water and increased irrigation water use efficiency (IWUE) by 41.3%. Rice cv. ‘PR 115’ recorded higher IWUE than cv. ‘PAU 201’ but had a statistically similar grain yield. Higher IWUE, waterexpense efficiency (WEE) and grain yield was recorded in three hand-weedings as compared to the sequential application of pre- and post-emergence herbicides. DSR sown on day of nursery sowing, coupled with short duration variety (PR 115) and three hand weedings produced statistically similar grain yield with higher IWUE as compared to transplanted crop.